Restoration of Massasauga Rattlesnake (Sistrurus C. Catenatus) Overwintering Habitat: Design, Construction and Ecohydrological Assessment - Lehan, Kieran (My University, 2020)
The eastern massasauga rattlesnake, or massasauga, is threatened in Ontario. Massasaugas overwinter in habitat that is sufficiently moist, above the water table, and below the zero-degree isotherm in a physical space conceptualized as a resilience zone. A development project in the Eastern Georgian Bay subpopulation of massasaugas overwintering habitat necessitated restoration. The Toronto Zoo hibernacula design was deemed inappropriate for use in this bedrock dominated landscape, as the limited deep groundwater percolation would result in flooding of the habitat from the fall to spring. Massasaugas in EGB, overwinter above the water table in Sphagnum peat hummocks. The ecohydrological factors of these hummocks in confirmed massasauga habitat were evaluated in a mixed effect linear model. It was found that taller hummocks, taller shrubs, and less WT variability were the best predictor of suitable conditions. This information was combined into a restoration method that moves surficial peat material from a soon to be impacted wetlands to an adjacent depression with mean depths of 40-80 cm, with mean bottom substrates 15-30 cm, and varying proportions of open water and floating peat with different vegetation communities. This design limits water table variability and allows for the growth of tall shrubs. Unforeseen circumstances meant that peat to be used in the project had to be stockpiled, which increased peat bulk density and limited photosynthesis. Despite this, restored habitat had similar mean lengths of unsuitable conditions compared to confirmed massasauga wetland habitat. The physical size of available overwintering habitat, as well as the total duration of unsuitable conditions, was not significantly different between restored wetlands, unconfirmed wetlands, and confirmed wetlands. Amendments to increase the cover of live Sphagnum moss will likely increase the duration and size of suitable conditions in the restored wetlands. Based on this success with degraded materials this new method of restoration design shows great promise in this region.
Keywords: Restoration; wetlands; Species at risk; overwintering; peatland; Sphagnum